Relations between Islam and Judaism in the Issue of Sexuality: Foucault's Discourse Analysis of QS. Al-Baqarah [2]: 222–223 - Niamillah, Nabil Muhammad; Arif, Mohammad; Lubaba, Gabriellea (Analisis: Jurnal Studi Keislaman, 2026)
The diversity of socio-religious constructions of menstruation and sexuality in 7th-century Medina society demonstrates the discursive relationship between early Islam and Jewish traditions regarding the female body, chastity, and sexual relations. The main problem of this research is how QS. Al-Baqarah [2]: 222–223 reshapes the meaning of menstruation, regulates bodily authority, and constructs sexual ethics of husband and wife in the context of Islamic-Jewish discourse relations. This research uses a literature study with a qualitative-historical approach and Michel Foucault's discourse analysis, specifically the archaeology of knowledge, genealogy, and technologies of the self. The main data are sourced from QS. Al-Baqarah [2]: 222–223, the asbāb al-nuzūl narrative, hadith, classical-contemporary interpretations, and Leviticus 15:19–33 as a comparative text. The research findings show that the Qur'an shifts the construction of menstruation from ritual impurity to adhā, a biological condition that requires ethical regulation without social exclusion. This verse also establishes the normative authority of Islam over the body and sexuality, while simultaneously shaping the Muslim subject who internalizes purity through the control of desire and ṭahārah. The novelty of this article lies in the reading of QS. Al-Baqarah [2]: 222–223 as a discursive text in the relationship between Islamic and Jewish discourse, thus expanding the study of interpretation from a normative-fiqh approach to a historical-sociological analysis of the body, sexuality, and the formation of the early Muslim religious subject.